The relation of magnetic properties and anomalous Hall behaviors in Mn4N (200) epitaxial films. (May 2018) - Li, Dan; Hu, Ping; Meng, Meng; Li, Hongwei; Wu, Shuxiang; Li, Shuwei
Graphical abstract: The temperature dependence of longitudinal resistivity (blue ball), fitting at high temperature (red star) and low temperature (green triangle). Inset is the relation of transverse resistivity, ordinary Hall resistivity, and anomalous resistivity curves. Highlights: Ferrimagnetic Mn4N(200) were grown on MgO(100) by plasma assisted molecular beam epitaxy. We elucidate the relation of nitrogen vacancies and the magnetism by adjusting the growth pressure. We state the relation of longitudinal resistivity and temperature as ρxx ∝T 1.9994 (T ≤ 86K) and ρxx ∝T 0.3068 (T > 86K) by data fitting. We introduce a method to estimate the Debye temperature of Mn4 N materials and the residual resistance of 0 K. We verify the linear relation between anomalou Hall resistivity (ρAH ) and magnetization at low magnetic field. Abstract: The Mn4 N(200) films were grown on MgO(100) substrates by molecular beam epitaxy. The saturated magnetizations are 0.735 μB/f.u. and 0.892 μB/f.u. under pressure of 7.5 × 10 −6 mbar –9.5 × 10 −6 mbar . Increasing of growth pressure enhances the magnetism of Mn4 N due to the reduction of nitrogen vacancies. Debye temperature (TD ) of Mn4 N is estimated to be 86 K . The longitudinal resistivity is linear to T 1.9994 when T < TD, which coincides with electron-electron scattering of ferromagnetic coupling. The longitudinal resistivity originates from electron-electron scattering below TD since electron-phonon scattering is frozen. The longitudinal resistivity at 0 K is about 10% lower than 5 K as 7.085 μΩ cm . Mn4 N films show obvious anomalous Hall Effect in perpendicular magnetic fields. The anomalous Hall resistivity ( ρAH ) of Mn4 N film is obtained by subtracting the ordinary Hall resistivity from transverse resistivity. The ρAH is verified to be linear to magnetization at low magnetic field strength region (0–9 KOe ).